Analysis on clarity of rubies gemstones using charge-coupled device (CCD) - Fatinah, Mohd Rahalim; Juliza, Jamaludin; Syarfa Najihah, Raisin; Irneza, Ismail; Yasmin, Abdul Wahab; Ruzairi, Abdul Rahim; Mus’ab, Sahrim; Sharma Rao, Balakrishnan; Wan Zakiah, Wan Ismail; Farah Aina, Jamal Mohamad; Nur Arina Hazwani, Samsun Zaini (Malaysian Society for Computed Tomography and Imaging (MyCT), 2021)
Ruby is one of the most precious gemstones on Earth that is always high in demand especially in the jewelry industries. Due to its high value and very expensive, a lot of imitation of ruby has been made. This results in the rising of more complicated issues as gemologists need to perform the grading valuation very carefully and precisely. The current and common grading techniques mostly depend on human vision, which eventually leads to error. This paper aims to analyze the clarity of rubies gemstonesusing Charge-Coupled Device (CCD). The CCD detects the light intensity and then convert the light intensity value into the voltage value. The CCD sensor is very special in its architecture design, consisting of morethan 1000 very small pixels that are sensitiveto light sources.Based on the previous research, CCD has high sensitivity to laser light source with wavelength range within 430 nm to 650 nm.This research is going to prove that CCD is able to detect the clarity of various grading of the pink to blood-red ruby stones.